DETERMINATION OF INDEX RISK OF RIVER BASIN VACACAÍ-MIRIM WITH THE USE OF INDICATORS OF DANGER AND VULNERABILITY - Kemerich, Pedro Daniel da Cunha; Martins, Sergio Roberto; Kobiyama, Masato; Borba, Willian Fernando de; Ritter, Luciana Gregory (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
With the increasing of pollution levels of water resources, whether it surface or underground, With the increasing levels of pollution of water resources, whether surface or underground, appear alternative that aim to establish methodologies used in estimating the natural vulnerability to contamination that aquifer presents. The hazard can be defined as a potential threat to humans and their welfare. Since the risk element can be the probability in which harmful occurrences, and they are economic, social or environmental, resulting from interactions between natural hazards and human systems. This study aim to determine risk, hazard and vulnerability to contamination in the river watershed Vacacaí-Mirim. To determine the vulnerability was used GOD methodology (Groundwaterhydraulicconfinement Overlayingstrata Depthtogroundwatertable). The risk was considered to be the product of the hazard estimated by vulnerability, the danger was obtained by reason of the Index of Potential Polluters of the Industry by Socioeconomic Development Index. For municipalities constituents of River watershed Vacacaí-Mirim, the socioeconomics index (income, health, and sanitation conditions of households and education) ranged from low to high. Regarding vulnerability to contamination, the values ranged from insignificant to extreme, values of Hazard and Risk ranged from Low / zero to very high. The danger ranged from low to very high, since the risk ranged between low / zero and very high.